Algorithmic Educational Management: When Algorithms Influence Educational Policy and Decision-Making - Nur Wahyuni (Gestion Educativa, 2026)
Algorithm-based educational management is an increasingly prominent phenomenon in the context of the digital transformation of modern educational systems. This article comprehensively examines how artificial intelligence algorithms and machine learning influence policy-making and decision-making in educational institutions. Through a systematic review of recent literature, this study identifies three main domains of algorithmic application in education: academic performance prediction, personalized learning, and institutional management optimization. The findings reveal that while algorithms can enhance the efficiency and accuracy of decision-making, serious challenges remain regarding transparency, algorithmic bias, data privacy, and ethical accountability. A holistic policy framework grounded in artificial intelligence ethics principles is needed to ensure that technology implementation supports educational equity and justice.